Determinar la eficacia y residualidad de las diferentes dosis de morfolinas para el control de sigatoka negra(Mycospherella fijiensis morelet) En el cultivo de banano en la zona de Mocache en los meses de febrero a abril del 2012 - Muriel Muñoz, Cindy Katherine (2012)
This research was conducted in the Research Field of Banana (RFB) of the Convention UTEQ-BASF located in the Faculty of Animal Science (FAS), the State Technical University Quevedo, Experimental Farm "La Maria", located at Km 7 ½ of the Milky Quevedo - The Empalme, Canton Mocache, Province of Los Ríos, whose geographical coordinates are 01 ° 0 '6 " south latitude and 79 ° 29' west longitude, 120 m, in an area of tropical rainforest (BHT). Target was raised generally determine the efficacy and residual Morpholine to control Black Sigatoka (Mycosphaerella fijiensis) from banana (Musa acuminata), Mocache area, during the high pressure in 2012. The specific objectives were to evaluate the effect of shock Morpholines to control Black Sigatoka in banana cultivation and measure the residual effect of the treatments applied in the crop. The experiment was subjected to the following hypotheses: H1 At least one of the treatments presented greater shock effect on the disease H2 At least one of the treatments at higher present in the residual disease control. Treatments were T1 Calixin by 0.5 l haˉ¹, T2 Volley 1 l haˉ¹, T3 Volley 0.7 l haˉ ¹, Agricultural Oil T4 and T5 absolute control. We used the design of randomized complete block, multiple range test was 0.05% Tukey. The effect of residual, measured this variable in area under the curve (AUC), giving the following results, treatments T2 Volley 1 l ha ˉ ¹ with an average of 56.98 AUC (Area Under the Curve), T3 Volley 0.7 l ha ˉ ¹ with an average ABC of 74.63, which was the best, T1 Calixin 0.5 l ha ˉ ¹ with ABC averaged 91.33, while the lower efficacy of crop oil were T4 and T5 with ABC 122.83 to 122.65 ABC absolute control. In the shock effect (control) was measured time of reinfection of the disease days after application (DAA), the treatments increased control were the T2 Volley 1 lha ˉ ¹ with 14 SD and T3 Volley 0.7 l ha ˉ ¹ with 12 dda, T1 0.5 lha Calixin ˉ ¹ 10 dda to reinfection, whereas lower efficacy were T4 and T5 Oil Agricultural absolute control with 0 DAA to reinfection.